Endomyometriosis of the Rectum With Disseminated Peritoneal Leiomyomatosis 8 Years After Laparoscopic Myomectomy: A Case Report - La Greca, Giorgio; Colarossi, Cristina; Di Mattia, Paolo; Gozzo, Cecilia; De Zuanni, Marco; Piombino, Eliana; Memeo, Lorenzo (Frontiers in Surgery, 2021)
Endomyometriosis is a rare finding and it can be challenging to diagnose and to treat. It can arise in the uterus, in the ovary, in the broad ligament, in the peritoneal surface and in other pelvic structures. Usually patients with endomyometriosis are asymptomatic, but symptoms could occur due to large dimensions or site of the mass. We present a case of a 49-year-old woman with a symptomatic pelvic mass in the rectal wall, with no history of endometriosis, who underwent laparoscopic myomectomy 8 years earlier.